Dynamics of Local Government Policy in Waste Management in Indonesia - Wahyu Maesarini, Indah (Iapa Proceedings Conference, 2023)
This article is written on the basis of the current condition of waste management problems in Indonesia, where problems in major cities in Indonesia have experienced a position in the waste emergency phase. Various forms of waste management that have been carried out by regions in Indonesia do not necessarily reduce the volume of accumulated waste generation and have become a common daily sight. This paper uses case studies from various major waste management cities in Indonesia. In general, the findings found that waste problems in various major cities in Indonesia are not spared from the dynamics that develop in their respective regions. It takes not only the ability but also the ability of local governments to commit to waste control in their respective cities through local government policies that are oriented towards clean, environmentally friendly, and innovative cities.